2008
DOI: 10.1136/jnnp.2007.116038
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing surgical outcome in patients with focal cortical dysplasia

Abstract: A total of 120 patients with histologically proven focal cortical dysplasias (FCD) were retrospectively analysed for prognostic factors for successful epilepsy surgery. Multivariate data analyses showed that older age at epilepsy surgery, occurrence of secondarily generalised seizures and a multilobar extent of the dysplasia were significant negative predictors. In univariate analyses, longer duration of epilepsy, need for intracranial EEG recordings and incomplete resection of the FCD were factors which signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 18 publications
5
49
2
4
Order By: Relevance
“…Resting EEG was recorded for 5 to 20 minutes prior to scanning sessions, and resting state EEG-fMRI was recorded for two or three 20-minute sessions as tolerated. Sessions consisted of 404 T2*-weighted single-shot gradient-echo echo-planar images (EPIs; echo time/repetition time, 30/3000 milliseconds; flip angle, 90°; 43 2.5mm interleaved slices; FOV, 24 × 24cm2; matrix, 64 × 64) acquired continuously on a 3T Signa Excite HDX MRI scanner (General Electric, Milwaukee, WI). EPI time series were realigned and spatially smoothed with a cubic Gaussian Kernel of 8mm full width at half maximum.…”
Section: Methodsmentioning
confidence: 99%
“…Resting EEG was recorded for 5 to 20 minutes prior to scanning sessions, and resting state EEG-fMRI was recorded for two or three 20-minute sessions as tolerated. Sessions consisted of 404 T2*-weighted single-shot gradient-echo echo-planar images (EPIs; echo time/repetition time, 30/3000 milliseconds; flip angle, 90°; 43 2.5mm interleaved slices; FOV, 24 × 24cm2; matrix, 64 × 64) acquired continuously on a 3T Signa Excite HDX MRI scanner (General Electric, Milwaukee, WI). EPI time series were realigned and spatially smoothed with a cubic Gaussian Kernel of 8mm full width at half maximum.…”
Section: Methodsmentioning
confidence: 99%
“…There was no significant difference in the postsurgical seizure outcome between patients with Palmini type I and type II cortical dysplasia in UCLA cohort 70 and in other epilepsy center. 71 However, some studies reported less favorable outcome in patients with Palmini type I cortical dysplasia, 72,73 and other studies reported opposite results, 74 although a significant proportion of these patients also had HS. Such inconsistent results among various studies also appear to be a major problem in elucidating the clinicopathological correlation of cortical dysplasia as being discussed in HS, and may be due, at least in part, to the difference in inclusion and exclusion criteria.…”
Section: Focal Cortical Dysplasiamentioning
confidence: 99%
“…Until recently, FCDs were mainly distinguished by the presence or absence of Balloon cells. Although the histological abnormalities in FCD with Balloon cells are more prominent than in FCD without Balloon cells, there is no difference regarding the severity of epilepsy [11,13-15]. In both patient groups a high seizure frequency and a pharmaco-resistant course of the disease is common [16-18].…”
Section: Introductionmentioning
confidence: 99%